2018
DOI: 10.4132/jptm.2018.09.20
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Immunocytochemistry of CD56 in Determining Malignancy from Indeterminate Thyroid Fine-Needle Aspiration Cytology

Abstract: BackgroundFine-needle aspiration cytology serves as a safe, economical tool in evaluating thyroid nodules. However, about 30% of the samples are categorized as indeterminate. Hence, many immunocytochemistry markers have been studied, but there has not been a single outstanding marker. We studied the efficacy of CD56 with human bone marrow endothelial cell marker-1 (HBME-1) in diagnosis in the Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) category III.MethodsWe reviewed ThinPrep liquid-based cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The overall accuracy of 91.2% in that study is comparable to the 100% accuracy of the current study [15]. A similar study performed in Korea to evaluate the usefulness of the CD-56 marker revealed that it has greater sensitivity and that combined use with the HBME-1 biomarker can increase the speci city [15]. Consistent with the ndings of the present study, George et al (2017) reported that the sensitivity and speci city of FNAC can increase by up to 98.88% and 99.11%, respectively, when immunocytomarkers are used [16].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The overall accuracy of 91.2% in that study is comparable to the 100% accuracy of the current study [15]. A similar study performed in Korea to evaluate the usefulness of the CD-56 marker revealed that it has greater sensitivity and that combined use with the HBME-1 biomarker can increase the speci city [15]. Consistent with the ndings of the present study, George et al (2017) reported that the sensitivity and speci city of FNAC can increase by up to 98.88% and 99.11%, respectively, when immunocytomarkers are used [16].…”
Section: Discussionsupporting
confidence: 78%
“…The current study ndings showed 100% concordance in immunocytochemistry and histology results, indicating the higher diagnostic speci city and malignant predictability of the immunocytochemistry technique. The overall accuracy of 91.2% in that study is comparable to the 100% accuracy of the current study [15]. A similar study performed in Korea to evaluate the usefulness of the CD-56 marker revealed that it has greater sensitivity and that combined use with the HBME-1 biomarker can increase the speci city [15].…”
Section: Discussionsupporting
confidence: 71%
“…In a recent study, researchers demonstrated that CD56 is a handy screening marker in thyroid cytology. CD56 showed high sensitivity (90%) and diagnostic accuracy (88.4%) in the diagnosis of the indeterminate lesion (Bethesda category III) 29. Although the overall diagnostic performance of CD56 is good,16 our results reveal the possible pitfall when using CD56 for preoperative diagnosis.…”
Section: Discussionmentioning
confidence: 68%
“…CD56 showed high sensitivity (90%) and diagnostic accuracy (88.4%) in the diagnosis of the indeterminate lesion (Bethesda category III). 29 Although the overall diagnostic performance of CD56 is good, 16 our results reveal the possible pitfall when using CD56 for preoperative diagnosis. Expression of CD56 in the tall cell variant, classic PTC with tall cell features, Warthin-like, or cribriformmorular PTCs will not cause misdiagnosis in the surgical specimen because the histologic characteristics of these variants are evident.…”
Section: Discussionmentioning
confidence: 78%
“…[42] Β-catenin 100% sensitive in cribriform morula variant of papillary thyroid carcinoma [43] HBME-1, CD15 HBME-1 is a sensitive marker for both usual type of papillary carcinoma and follicular variant papillary thyroid carcinoma, Sensitivity is low and specificity is high in CD15 [44] CD79a, CD 03, CD 30, cytkeratin FNAC in combination with immunocytochemistry increases the diagnostic efficacy of thyroid lymphoma. [45] CD 147 CD147 expression correlates significantly with the degree of dedifferentiation of thyroid carcinoma [46] CD56, HBME-1 CD-56 has a low specificity with a high sensitivity. Combination of CD56 with HBME-1 increases the specificity.…”
Section: Research Immunocytochemical Markers Used Diagnosismentioning
confidence: 99%